2009
DOI: 10.1159/000251174
|View full text |Cite
|
Sign up to set email alerts
|

A Holistic Approach to Androgen Deprivation Therapy: Treating the Cancer without Hurting the Patient

Abstract: Introduction: Androgen deprivation therapy (ADT) for advanced prostate cancer can be associated with side effects which may negatively impact quality of life (QoL) and induce serious medical problems. Aim: The aim is to give practical recommendations on how to monitor and counsel patients and effectively manage side effects based on relevant original articles, review articles and abstracts. Results: Urologists should be aware of side effects and adapt their practice patterns to rapidly recognize these and admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 66 publications
(64 reference statements)
0
25
0
Order By: Relevance
“…effects on serum testosterone and hemoglobin 1,[7][8][9][10] . Recent studies have confirmed a decline in serum hemoglobin attributable to these newer approaches to tab-and also a variety of other side effects, including metabolic disorders, cardiovascular disease, hot flashes, sexual dysfunction, depressed mood, muscle weakness, and osteoporosis 2,7,[11][12][13][14][15][16][17] .…”
Section: Resultsmentioning
confidence: 99%
“…effects on serum testosterone and hemoglobin 1,[7][8][9][10] . Recent studies have confirmed a decline in serum hemoglobin attributable to these newer approaches to tab-and also a variety of other side effects, including metabolic disorders, cardiovascular disease, hot flashes, sexual dysfunction, depressed mood, muscle weakness, and osteoporosis 2,7,[11][12][13][14][15][16][17] .…”
Section: Resultsmentioning
confidence: 99%
“…92 Therefore, whenever possible, partners should be included in the treatment decision and consent process and provided adequate and appropriate support. 93 A multidisciplinary 'survivorship' team approach should exist for the management of ADT patients and their partners. Such a programme, should probably be called an 'ADT management programme' since the word 'survivorship' is not always properly understood and may lead patients to think that they may not survive ADT.…”
Section: Resultsmentioning
confidence: 99%
“…They are considered one of the most common and the most troublesome side effects since they appear in more than 80% of patients with prostate cancer treated with hormonal therapy [10]. Hot flashes are often caused by so-called trigger factors, which include stress, heat, a sudden change in body position, stimulants (coffee, cigarettes, alcohol) and consumption of spicy food [11, 12]. As non-pharmacological measures it is advised to avoid the aforementioned generative triggers, wear clothes made of natural fibers such as linen or cotton, use cold compresses to the neck or drink a glass of cold drink at the onset of symptoms and take regular exercise [11].…”
Section: Hot Flashesmentioning
confidence: 99%
“…Hot flashes are often caused by so-called trigger factors, which include stress, heat, a sudden change in body position, stimulants (coffee, cigarettes, alcohol) and consumption of spicy food [11, 12]. As non-pharmacological measures it is advised to avoid the aforementioned generative triggers, wear clothes made of natural fibers such as linen or cotton, use cold compresses to the neck or drink a glass of cold drink at the onset of symptoms and take regular exercise [11]. If burdensome symptoms keep occurring even after the change of lifestyle according to the recommendations mentioned above, it is advisable to include hormonal drugs: megestrol, cyproterone, nadroxyprogesterone or diethylstilbestrol in low doses.…”
Section: Hot Flashesmentioning
confidence: 99%
See 1 more Smart Citation